An investigation and a critical incident technique analysis on professional values of post-90s nursing students ("90后"护生职业价值观调查及关键事件研究) - LU Jianping (鲁剑萍); SUN Huijun (孙慧君) (Journal of International Translational Medicine Limited, 2021)
Objective To explore professional values of post-90s nursing students and related influencing factors. Methods The Nurses' Professional Value Scale was used to investigate 141 post-90s nursing students, and critical incident technique with an open-ended questionnaire was adopted to collect qualitative data. Results The score for each item of Nurses' Professional Value Scale was more than 3. 0-point. The univariate analysis showed that male students scored lower than female students (P＜0. 05), junior college student scored higher than undergraduate students, and there was no significant difference between students with and without first-choice degree (P＞0. 05). The multivariate analysis showed that choice of willingness, professional preference and education level were independent influencing factors of professional value. The critical incident technique analysis showed that positive events, especially social support and family care, were key factors to enhance the professional value of nursing students. Clinical practice was considered as an important part in the process of role transition from graduate to staff nurse. Conclusion The professional values of nursing students were generally neutral and positive. Their professional values can be influenced by many factors. It is required to form positive professional values from many angles. (目的 探讨"90后"护生职业价值观及其相关影响因素。方法 采用护士职业价值观量表对141名"90后"实习护生进行调查。应用关键事件技术, 通过开放性问卷调查收集影响护生职业价值观的关键事件。结果 实习护生职业价值观各条目均分均在3分以上, 为中等以上水平, 说明实习护生总体职业价值观良好。单因素分析显示, 男护生职业价值观评分比女护生低, 大专护生职业价值观评分较护理本科生高(P＜0. 05), 是否是第一志愿对护生的职业价值观的影响差异无统计学意义(P＞0. 05)。多因素分析显示, 生源类别、专业的喜爱程度和学历是影响护生职业价值的重要因素。关键事件研究中, 正面事件是提升护生职业价值的关键因素, 其中社会的支持和家人的关怀是最重要的因素。临床实习是护生转变为护士过程中重要的环节。结论 "90后"护生的职业价值观总体中立偏积极, 其职业价值观受较多因素影响, 相关部门应从多方面入手, 促进"90后"护生形成积极的职业价值观。)